2022
DOI: 10.1111/jipb.13263
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and genotype independent maize transformation using pollen transfected by DNA‐coated magnetic nanoparticles

Abstract: Current gene delivery methods for maize are limited to specific genotypes and depend on time‐consuming and labor‐intensive tissue culture techniques. Here, we report a new method to transfect maize that is culture‐free and genotype independent. To enhance efficiency of DNA entry and maintain high pollen viability of 32%‐55%, transfection was performed at cool temperature using pollen pretreated to open the germination aperture (40%–55%). Magnetic nanoparticles (MNPs) coated with DNA encoding either red fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Besides directly interfacing with plants, nanomaterials are also used as platforms to deliver cargo to plants. For example, Fe 3 O 4 NPs ( Zhao et al., 2017b ; Wang et al., 2022a ) and single-walled carbon nanotubes ( Demirer et al., 2019 ; Kwak et al., 2019 ) have been used to deliver DNA to enable transgenic events in non-model plant species such as wheat and cotton. Clay nanosheets ( Mitter et al., 2017 ), DNA nanostructures ( Zhang et al., 2019a ), gold nanoclusters ( Zhang et al., 2021 ), and AuNPs ( Zhang et al., 2022 ) have been used to deliver siRNA to enable RNA silencing in plants.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides directly interfacing with plants, nanomaterials are also used as platforms to deliver cargo to plants. For example, Fe 3 O 4 NPs ( Zhao et al., 2017b ; Wang et al., 2022a ) and single-walled carbon nanotubes ( Demirer et al., 2019 ; Kwak et al., 2019 ) have been used to deliver DNA to enable transgenic events in non-model plant species such as wheat and cotton. Clay nanosheets ( Mitter et al., 2017 ), DNA nanostructures ( Zhang et al., 2019a ), gold nanoclusters ( Zhang et al., 2021 ), and AuNPs ( Zhang et al., 2022 ) have been used to deliver siRNA to enable RNA silencing in plants.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Engineered nanomaterials have been proposed as ideal platforms for leading the agri-technology revolution ( Lowry et al., 2019 ). For example, efforts have been made to deliver genetic materials such as DNA ( Torney et al., 2007 ; Lakshmanan et al., 2013 ; Zhao et al., 2017a ; Demirer et al., 2019 ; Kwak et al., 2019 ; Wang et al., 2022a ), RNA ( Mitter et al., 2017 ; Zhang et al., 2019a , 2022 ; Demirer et al., 2020 ), and proteins ( Ng et al., 2016 ; Santana et al., 2020 ; Wang et al., 2021 ; Watanabe et al., 2021 ) to plants. Using a plant nanobionics approach, bomb-detecting plants (plants as detectors of explosive chemicals) ( Wong et al., 2017 ), light-emitting plants ( Kwak et al., 2017 ), and smart plant sensors ( Giraldo et al., 2019 ) have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Similar methods have also been reported in maize. It has been found that pollen can absorb DNA nanoparticles with high ability under specific conditions; maize embryos have been confirmed to contain GUS genes transferred by magnetic nanoparticles [ 73 ]. Similarly, the offspring of transgenic maize displayed the desired features of foreign genes vividly showed as the Figure 3 .…”
Section: Nanomaterial-induced Gene Delivery Systemsmentioning
confidence: 99%
“…However, studies have shown that foreign DNA delivered into cotton and maize pollen cells using magnetic nanomaterials indeed integrated into the genome. Moreover, the expression of reporter genes, such as GUS and GFP, have been detected in progeny seedlings [ 72 , 73 ], demonstrating the stable integration and inheritance of exogenous DNA. However, detailed analyses, such as the identification of the integration sites and the border sequences of the integrated foreign DNA, remain to be conducted.…”
Section: Future Prospects For Plant Genetic Engineering With Nanomate...mentioning
confidence: 99%
“…Hence, the transformation of pollen grains to modify the maize genome may be completed within several hours and can be performed in the field. This novel transformation system may be applicable for crops lacking an established tissue culture regeneration system (e.g., some fruit trees and other horticultural crops) [ 143 ]. This method may expand the range of crops that can be genetically modified by the CRISPR/Cas9 system.…”
Section: Technical Problems Associated With the Crispr/cas9 System An...mentioning
confidence: 99%